In Vitro Production and Identification of Angiotensin Converting Enzyme (ACE) Inhibitory Peptides Derived from Distilled Spent Grain Prolamin Isolate - Dong Wei; Wenlai Fan; Yan Xu (Foods, 2019)
Distilled spent grain (DSG), the biggest by-product of the Chinese liquor industry, is rich in protein (167.8 g/kg DSG dry weight (DW)). Accounting for 60% of the total protein, prolamins are isolated from dried DSG (DDSG). In this study, angiotensin-converting enzyme (ACE) inhibitory peptides were screened from the prolamin hydrolysates of DDSG using two independent active-directed separations, ultrafiltration and reversed phase high performance liquid chromatography (RP-HPLC) coupled with ACE inhibitory activity evaluation. Six novel ACE inhibitory peptides, AVQ, YPQ, NQL, AYLQ, VLPVLS, and VLPSLN, were successfully identified and quantified from the active RP-HPLC fractions. AVQ and YPQ exhibited the highest activity, having the concentration inducing 50% inhibition (IC50) values for ACE of 181.0 and 220.0 μM, respectively. It was observed that VLPVLS was the most abundant peptide (16.96 mg/g DW) in prolamins. The results indicated that prolamin hydrolysates from DDSG could be served as a source of ACE inhibitory peptides.